2022
DOI: 10.1037/cep0000292
|View full text |Cite
|
Sign up to set email alerts
|

Aging and directed forgetting: Evidence for an associative deficit but no evidence for an inhibition deficit.

Abstract: Intentional forgetting aims to prevent unwanted information from being stored in long-term memory. Surprisingly, past research has shown that, relative to younger adults, older adults recall and recognize more to-be-forgotten information. It has been suggested that this occurs because older adults have a deficient ability to inhibit information. In two experiments, we examined memory differences between older and younger adults in an item-method directed forgetting task. Participants viewed words one at a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Our general findings are similar to a recently published itemmethod directed forgetting study with an online sample who also reported an overall directed forgetting effect, but no age-related deficits in forgetting compared to younger adults (Tanberg et al, 2022). There are other empirical exceptions to age-related deficits in forgetting, including when the older participant is not personally responsible for remembering the information, TBF information is not goal relevant, or TBF is presented in a more applied context (e.g., McGillivray & Castel, 2017;Murphy & Castel, 2022).…”
Section: Does Reward Motivation Improve Directedsupporting
confidence: 90%
See 2 more Smart Citations
“…Our general findings are similar to a recently published itemmethod directed forgetting study with an online sample who also reported an overall directed forgetting effect, but no age-related deficits in forgetting compared to younger adults (Tanberg et al, 2022). There are other empirical exceptions to age-related deficits in forgetting, including when the older participant is not personally responsible for remembering the information, TBF information is not goal relevant, or TBF is presented in a more applied context (e.g., McGillivray & Castel, 2017;Murphy & Castel, 2022).…”
Section: Does Reward Motivation Improve Directedsupporting
confidence: 90%
“…The cognitive mechanisms used in an item-method directed forgetting task, particularly in older age, are still debated. Explanations include differential encoding for TBR versus TBF items (Basden, 1996; Basden et al, 1993; Bjork, 1989; Bjork & Woodward, 1973; MacLeod, 1989, 1999, 2012; Sahakyan et al, 2008; Titz & Verhaeghen, 2010) particularly attentional inhibition and suppression of TBF information (Rizio & Dennis, 2013, 2014; Van Hooff et al, 2009; Zacks et al, 1996, 2000), cognitive load and working memory capacity limits (Popov et al, 2019), and deficits in associative binding in older age (Tanberg et al, 2022), as well as evidence that the mechanisms or strategy may change depending on the specifics of the experimental design (Lee, 2012; Sego et al, 2006). The strategies used to remember and forget may be different and may not interact with reward in the same way, but we did not design our experiments to test these different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation